COLLABORATIVE LEARNING IN ENGINEERING: DEVELOPING TEAMWORK AND PROBLEM-SOLVING SKILLS - Renuka Patel (PT. Radja Intercontinental Publishing, 2024)
Engineering education, emphasizing the development of teamwork and problem-solving skills essential for modern engineering practice. This study explores the impact of collaborative learning environments on engineering students' ability to work effectively in teams and tackle complex problems. Through a combination of qualitative and quantitative research methods, including surveys, interviews, and performance assessments, the study evaluates students' skill development over a semester-long course designed with collaborative projects. Findings indicate significant improvements in communication, coordination, and conflict resolution abilities, as well as enhanced problem-solving proficiency. The research highlights the importance of structured teamwork activities and reflective practices in fostering these essential skills, suggesting that collaborative learning should be an integral component of engineering curricula to better prepare students for the demands of the professional engineering environment.